2018
DOI: 10.1039/c8ra00210j
|View full text |Cite
|
Sign up to set email alerts
|

Excimer based fluorescent pyrene–ferritin conjugate for protein oligomerization studies and imaging in living cells

Abstract: Ferritin self-assembly has been widely exploited for the synthesis of a variety of nanoparticles for drugdelivery and diagnostic applications. However, despite the crucial role of ferritin self-assembly mechanism for probes encapsulation, little is known about the principles behind the oligomerization mechanism. In the present work, the novel "humanized" chimeric Archaeal ferritin HumAfFt, displaying the transferrin receptor-1 (TfR1) recognition motif typical of human H homopolymer and the unique salttriggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…To circumvent these difficulties, a highly reactive cysteine per monomer was introduced by a point mutation as reported elsewhere. 20 , 37 This mutation (M54C) in the protein inner cavity offers the opportunity to covalently conjugate up to 24 thiol-reactive linkers, such as maleimide- or pentafluorobenzenesulfonamide-based compounds bearing positively charged side-chains ( PAs ) at pH 7.4 as predicted by ab initio calculation ( Figure S26 ). As illustrated in Scheme 3 , chemical conjugations were performed using the assembly disassembly mechanism of HumAfFt in very mild conditions, at pH 8.3, to promote the nucleophilic reaction between thiols and PAs linkers.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent these difficulties, a highly reactive cysteine per monomer was introduced by a point mutation as reported elsewhere. 20 , 37 This mutation (M54C) in the protein inner cavity offers the opportunity to covalently conjugate up to 24 thiol-reactive linkers, such as maleimide- or pentafluorobenzenesulfonamide-based compounds bearing positively charged side-chains ( PAs ) at pH 7.4 as predicted by ab initio calculation ( Figure S26 ). As illustrated in Scheme 3 , chemical conjugations were performed using the assembly disassembly mechanism of HumAfFt in very mild conditions, at pH 8.3, to promote the nucleophilic reaction between thiols and PAs linkers.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that at a lower salt concentration (0.01 M) emission quenching was less for NDI-OL, whereas at higher salt concentration (1 M) emission quenches by the following order; NaNO 2 > NaF > NaBr > Na 2 SO 3 � NaCl as seen for 464 and 556 nm emission respectively for NDI-OL and NDI-OD. [48] It is observed that at higher ionic strength does influence the excimer emission regardless of nature of salt and counter ion and the extensive quenching observed in the case of NO 2 À could be viewed as the effect of quenching by nitrite ions than the of ionic strength. Further, the effect of pH was studied in THF/water (1 : 99, v/v) mixture at varied pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Aggregation Induced Enhanced Emission (Aiee) and Mechanochromic Behaviourmentioning
confidence: 98%
“…Such procedure, however, is not amenable to the encapsulation of most proteins that display both acid or alkaline folding instability. In contrast, the ferritin from Archaeglobus fulgidus (AfFt) has emerged as an alternative to human ferritin homopolymers as it requires mild cargo material encapsulation conditions in view of the unique self-assembly properties that entail divalent cation driven assembly at neutral pH values 11 . AfFt assembles in a distinctive tetrahedral geometry as a result of a particular packing between four hexameric units into a unique 24-mer structure, which results in the formation of four wide triangular pores (45 Å) on the protein shell 12,13 .…”
Section: Introductionmentioning
confidence: 99%